Analysis of QRIS's Role in Encouraging Indonesia's Financial Inclusion and Digital Economic Growth Using Qualitative Methods with a Phenomenological Approach - Azerwin Barchia; Irwan Bastian; Dewi Agushinta R. (Dinasti International Journal of Education Management and Social Science, 2025)
Quick Response Code Indonesian Standard (QRIS) is one of the innovations in digital payment systems that are increasingly used by MSMEs in Indonesia. This study aims to understand the role of QRIS in increasing sales and profitability of MSMEs, specifically a coffee shop in East Jakarta. This research employs a qualitative method with a phenomenological approach to explore the experiences of coffee shop owners and customers in using QRIS. It was conducted through several stages, including problem identification, data source selection, data collection (interviews, participatory observation, and documentation), data analysis, data validation, and presentation of findings. The respondents in this study consist of three coffee shop owners and fourteen customers who use QRIS. The findings show that QRIS helps coffee shop owners record transactions digitally, reduces the risk of losing cash, and enhances customer convenience. Some challenges were identified, such as network disruptions and infrastructure limitations. QRIS plays an important role in promoting financial inclusion by facilitating MSMEs' access to formal financial services, such as loans and other facilities. The success of QRIS in driving the largely digital economy depends on government support, clear regulations, and adequate infrastructure.